Determinants of Household Happiness in Indonesia - Vitriyani Tri Purwaningsih; Nindya Eka Sobita; Mega Mariska; Muhammad Mufti Hudani; Rizka Malia; Dian Fajarini (West Science Journal Economic and Entrepreneurship, 2024)
One of the dimensions that the BPS uses to gauge happiness is life satisfaction. The elements influencing home happiness in Indonesia are examined in this study. Households with secondary data from the Indonesia Family Life Survey (IFLS) comprise the study's sample. This study's model analysis makes use of logistic regression. According to the study's findings, possessions including a home, a car, savings, and even jewelry are among the things that influence household satisfaction in Indonesia. In addition, other factors such as health, ownership of electronic goods, internet access and the area of residence outside Java will increase household happiness. Overall, this study concludes that the more assets, the healthier the family condition and the easier the access, the more satisfied and happy the household will feel.